Pelatihan Pengenalan Artificial Intelligence (AI) pada Projek Penguatan Profil Pelajar Pancasila untuk Meningkatkan Kompetensi Guru pada Transformasi Digital di DKI Jakarta - Septian Mukhlis; Bramianto Setiawan; Gina Asri Ruwaida; Zulela MS; Elvina Nur Febriyani; Marissa Eva Listiani (Pusmedia Group Indonesia, 2025)
Digital transformation in the world of education requires teachers to have competencies that are relevant to technological developments, including an understanding of Artificial Intelligence (AI). This study aims to describe the implementation of AI introduction training in the context of the Pancasila Student Profile Strengthening Project (P5) as an effort to improve teacher competency in DKI Jakarta. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation of the implementation of the training. The results of the study indicate that AI introduction training associated with Pancasila values in P5 is able to build teacher awareness of the importance of implementing technology in the learning process. In addition, this training makes a real contribution to improving teachers' digital competencies, especially in terms of critical, collaborative, and innovative thinking. With this training, teachers are better prepared to integrate AI technology into the independent curriculum, creating an adaptive and transformative learning environment. The implications of this activity encourage the need for sustainable technology-based training programs for teachers to answer the challenges of 21st century education.